PENGARUH MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN STEM TERHADAP HASIL BELAJAR KOGNITIF PADA PEMBELAJARAN FISIKA DI SMA - Yullya Erlina Eka Putri; Albertus Djoko Lesmono; Lailatul Nuraini (Universitas Jember, 2021)
The student's activeness in the learning process is indispensable especially in the application of the curriculum 2013. Physics learning conducted in schools is still centered on teachers using lecture methods, so students tend to be passive, bored, and less enthusiastic in learning. Therefore, a learning model is needed can make students be centers during the learning process. This study aims to examine significant differences in students' cognitive learning outcomes when using the Problem Based Learning model with STEM approaches to Business and Energy materials. This type of research is a quasi-experiment and the research design used is pretest and posttest control-group design. The sample of this study is class X IPA 1 and X IPA 3 at MAN 2 Jember. Data collection of cognitive learning outcomes is obtained through tests. The data analysis conduct using the Independent Sample T-Test or Mann-Whitney U. Based on the results of the research, there was an improvement in cognitive learning outcomes between the experimental class and the control class after treatment. However, after being test using Mann-Whitney U showed no significant differences between cognitive learning outcomes between the experimental class and the control class. Key word: Cognitive Learning Outcomes, Problem Based Learning, STEM Approach